Overview [In West African agriculture and climate change: A comprehensive analysis] - Jalloh, Abdulai; Faye, Mbène Dièye; Roy-Macauley, Harold; Sérémé, Paco; Zougmoré, Robert B.; Thomas, Timothy S.; Nelson, Gerald C. (International Food Policy Research Institute, 2013)
This chapter provides an overview of the region, its current economic situ¬ation, and its vulnerability to climate change. It is designed to provide useful input into the efforts of ECOWAS in developing appropriate policies related to climate for the region. This chapter is followed by one that describes the common methodologies used by the authors of all country chapters and then by the individual country chapters. The monograph ends with a chapter that draws lessons for the region from the individual country studies.